PENINGKATAN SIKAP ILMIAH SISWA MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI MOMENTUM DAN IMPLUS - Richa Elianora; Azizahwati Azizahwati; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The developed Instructional tools used cooperative-based model with Guided Inquiry-learning which implemented in Physics material of Momentum and Impluses for the first year students of SMA, consisting of Lesson Plan (RPP), Students’ Worksheet (LKPD), and scientific questionnaires. The purpose of this study is to find out students’ scientific attitude and the type of this research is pre-experiment research of One Group Pretest-Posttest Design, the data used in this study was the data from students’ scientific attitude during the learning process. The instrument used in this study was the questionnaires of students’ scientific attitude. The questionnaires of scientific attitude was adapted from the questionnaires which developed by Afrianti (2016). Based on the results of a descriptive analysis which obtained from the students’ scientific scores that assessed from every scientific aspects which consist of curiousity, open mind, critical thinking and honesty. From the result, it can be seen that each indicator of scientific attitudes is increasing after the application of Guided Inquiry -learning in Momentum and Impulses material. With the increased of scientific attitudes, the students’ average scientific scores are also increased. In the early scientific attitude, the average score was 2.46 in low category and increased to 1.11 points on the final scientific attitude with an average score 3.56 in high category. Therefore, the Instructional Tools which developed by using Guided Inquiry-learning are able to enhance students’ scientific attitude.Key Words: Students’ Scientific Attitude, Guided Inquiry, Momentum impulses